In vitro embryo outgrowth is a bioassay of in vivo embryo implantation and development - Natalie K. Binder; Natalie J. Hannan; David K. Gardner (Asian Pacific Journal of Reproduction, 2015)
Objective: To determine the efficacy of embryo outgrowth on fibronectin as a low cost, high throughput alternative to embryo transfer to model embryo attachment and the initial stages of implantation. Methods: Following in vitro embryo culture, embryo quality was assessed via embryo transfer or embryo outgrowth with metabolic assessment. Results: This study shows that blastocysts attach to fibronectin at the same rate that they implant in vivo, and that the carbohydrate utilisation of embryos that successfully outgrow is comparable to those that are able to develop into a fetus. Conclusions: Embryo outgrowth is a suitable alternative endpoint to embryo transfer.